Building a semantic Web for securing the homeland. - Guzman, N.J.
Substantial advances in the application of semantic Web technologies arc already occurring in digital library science and among the intelligence communities. Knowledge management for homeland security is one of the most important benefits that will derive from these technologies in the near future. In this article, some of the problems that the semantic Web aims to address, the building blocks that will enable its implementation, and some early efforts in the use of semantic Web technologies for homeland security are reviewed.
Keywords: RDF; XML; Description logics; Frame-based systems; Homeland security; Information overload; Knowledge representation; Semantic Web technologies